La recepción de la Revolución Mexicana en América del Sur - Palacios, Guillermo (Jahrbuch für Geschichte Lateinamerikas, 2017)
This article studies the reaction of the governments, and, in some cases, of the public opinion of the more politically active countries in South America, when confronted with the Mexican revolutionary movements of 1910. It follows the steps of the reformists processes, strongly oriented towards the left side of the political spectrum, from the beginning of the 1920’s until the years of the Spanish Civil War. The central argument proposes that the South American governments, most of them from an oligarchic-rightist extraction, firmly allied with the United States, maintained diplomatic missions in Mexico City basically due to the country’s condition of a laboratory for radical leftist reforms that could very well spread to the south of the continent. Information was needed to prevent contamination. Furthermore, the article discusses the opportunity of the so-called Mexican Revolution represented for the failed efforts of the ABC block – Argentina, Brazil, Chile – towards the consolidation as the hegemonic political formation of Latin America, and the role the overheated political environment of México City played in the re-enacting of South America’s old territorial disputes.
Keywords: Mexican Revolution; South American Governments; Social Reforms; Leftist Radicalism; ABC